Monitoring 3D vibrations in structures using high‐resolution blurred imagery. (September 2016) - McCarthy, David M. J.; Chandler, Jim H.; Palmeri, Alessandro
Abstract: Photogrammetry has been used in the past to monitor the laboratory testing of civil engineering structures using multiple image‐based sensors. This has been successful, but detecting vibrations during dynamic structural tests has proved more challenging because they usually depend on high‐speed cameras which often results in lower image resolutions and reduced accuracy. To overcome this limitation, a novel approach has been devised to take measurements from blurred images in long‐exposure photographs. The motion of the structure is captured in individual motion‐blurred images without dependence on imaging speed. A bespoke algorithm then determines each measurement point's motion. Using photogrammetric techniques, a model structure's motion with respect to different excitation frequencies is captured and its vibration envelope recreated in 3D. The approach is tested and used to identify changes in the model's vibration response.